Correlation between the onset of parametric instability of lower hybrid waves and modification in edge plasma current profile on EAST. (28th September 2018) - Ding, B.J.; Li, M.H.; Li, Y.C.; Cesario, R.; Tuccillo, A.A.; Parker, R.; Baek, S.G.; Wang, Y.F.; Liu, H.Q.; Xu, J.C.; Wang, M.; Hu, H.C.; et al.
Abstract: The plasma current profile modification in the edge region is observed in LHCD (lower hybrid current drive) plasmas for the first time in EAST, correlated with an increased level of PI (parametric instability) activities with the decrease in LH (lower hybrid) source frequency or the increase in plasma density. With the increase in the PI strength, an increase in the edge current is observed despite of a reduction in current drive capability. In these plasmas, strike-point splitting behaviors are also observed, implying the modification of the magnetic geometry in the scrape-off-layer. Results show the effects of LH frequency and plasma density on power dissipation in the edge region, suggesting a role of anomalous wave power damping on the modification of current profile at the plasma edge. These novel results are significant in that they give insight for the first time into how nonlinear wave-plasma interactions such as PI may directly impact the edge current profile, the control of which is critical in order to achieve optimized modes of operation in a steady state fusion reactor.